Improving Learning Outcomes through Problem Based Learning (PBL) in Data Presentation for Elementary School Students - Novita, Dias; Hasanah, Miftahul; Rahmawan, Setia; Istiqomah (Reforma: Jurnal Pendidikan dan Pembelajaran, 2025)
The learning outcomes of fifth-grade students at Muhammadiyah Elementary School Sumberejo, particularly in mathematics, remain relatively low. This is due to the use of learning models that lack variety and still rely heavily on the lecture method. Consequently, student engagement in the learning process is low. This study aims to implement the Problem Based Learning (PBL) model on data presentation to improve learning outcomes for fifth-grade students at Muhammadiyah Elementary School Sumberejo. We employed Classroom Action Research (CAR) as the research method, involving 20 fifth grade students comprising 9 male and 11 female as the research subjects. Data were collected using written test and observation. The collected data were the analyzed using descriptive-comparative method. The results revealed a significant increase in learning outcomes, with mastery levels rising from 30% in the pre-cycle to 100% in cycle II. These findings suggest that PBL is an effective model for improving student engagement and learning outcomes, offering valuable insights for educators seeking to enhance mathematics instruction at the elementary school level.